2005
DOI: 10.1007/s00449-004-0389-6
|View full text |Cite
|
Sign up to set email alerts
|

MIR spectroscopic analysis on sugar metabolic and ethanol productive kinetics of suspension TBY-2 and rice cells pre-cultured in various media

Abstract: The influence of sugars in pre-cultivation media suspended plant cells on the kinetics of the sugar uptake and the ethanol production was studied by mid-infrared spectroscopy using a Fourier transform infrared spectrometer (FT-IR) equipped with an attenuate total reflection accessory (ATR). We performed the plant cell cultivation with Nicotiana tabacum cv. Bright Yellow No.2 (TBY-2) cells and Oryza sativa L., Japonica, cv. Nipponbare (rice) cells, respectively, in pre-culture and culture media, which had vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…This indicated that a part or most of the trehalose in the medium was hydrolyzed to glucose, which was consumed by the TBY-2 cell. Moreover, in the sucrose medium, the sucrose concentration decreased with an increase in the glucose and fructose concentrations, which the sucrose in the medium was hydrolyzed similar to the previous studies [13][14][15][16]32]. In contrast to these results, in the maltose medium, we rarely observed any sugar other than maltose by both the FT-IR/ATR and HPLC method (data not shown).…”
Section: Resultssupporting
confidence: 61%
See 4 more Smart Citations
“…This indicated that a part or most of the trehalose in the medium was hydrolyzed to glucose, which was consumed by the TBY-2 cell. Moreover, in the sucrose medium, the sucrose concentration decreased with an increase in the glucose and fructose concentrations, which the sucrose in the medium was hydrolyzed similar to the previous studies [13][14][15][16]32]. In contrast to these results, in the maltose medium, we rarely observed any sugar other than maltose by both the FT-IR/ATR and HPLC method (data not shown).…”
Section: Resultssupporting
confidence: 61%
“…The ATR spectra were obtained with a horizontal zinc selenide ATR sampling accessory (GRASEBY SPE-CAC, SPECACLAMP ATR 11080). The dry cell weight after drying was compared to the turbidity of culture medium by at 600 nm as described previously [13][14][15][16]28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations